Morphological evaluation of advanced breeding lines of rapeseed-mustard for salinity tolerance using multivariate and genetic analyses (Journal of the Bangladesh Agricultural University, 2020)
Salinity is a barrier of crop production while salinity affected areas are expanding in Bangladesh. To increase oilseed production in saline soils, a useful tactic could be developing salinity tolerant mustard varieties. This study screened advanced breeding lines of rapeseed-mustard along with a check variety for salinity tolerance. An experiment was conducted for multivariate and genetic assessments following a split plot design with six genotypes (BD-6950, BD-7104, BD-10115, JUN- 536, BJDH-12 and BARI Sarisha-14 as a check) and five salinity treatments (0, 6, 8, 10 and 12 dSm- 1). A total of 16 morphological characters were recorded. Significant variations were accounted among the genotypes and treatments for all the characters. A significant and positive correlation was found among seed yield plant-1 and 1000-seed weight, number of seeds siliquae-1, length of siliqua, length of primary branches. All morphological characters except number of secondary branches and length of siliqua showed high heritability, from 62% to 98%, which indicated that these characters can be selected for further improvement. Genetic analyses revealed high heritability with genetic advance in percentage of mean for number of seeds siliquae-1, number of siliqua in primary axis, number of siliqua in secondary axis, total siliqua plant-1 and seed yield plant-1 signifying their suitability as indicators for salinity tolerance. Principal component analysis revealed that days to first flowering and days to maturity were contrasting with other variables for salinity stress tolerance in the genotypes BD-7104 and BD-10115 under 8 and 10 dSm-1 salinity levels. Based on the multivariate analyses, the genotype BD-7104 followed by BD-10115 were revealed as the most suitable salt tolerant genotypes which can greatly contribute to oilseed production in saline prone areas. Further researches emphasizing QTL mapping of salt tolerant traits in order to develop new, improved and climate smart salt tolerant variety of oilseed Brassica are suggested.J Bangladesh Agril Univ 18(2): 323–331, 2020https://doi.org/10.5455/JBAU.82264